2016
DOI: 10.1093/schbul/sbw012
|View full text |Cite
|
Sign up to set email alerts
|

Disconnection Between Amygdala and Medial Prefrontal Cortex in Psychotic Disorders

Abstract: Distracting emotional information impairs attention more in schizophrenia (SCZ) than in never-psychotic individuals. However, it is unclear whether this impairment and its neural circuitry is indicative generally of psychosis, or specifically of SCZ, and whether it is even more specific to certain SCZ symptoms (eg, deficit syndrome). It is also unclear if this abnormality contributes to impaired behavioral performance and real-world functioning. Functional imaging data were recorded while individuals with SCZ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 133 publications
(142 reference statements)
0
33
0
Order By: Relevance
“…But neurophysiological evidence of impaired temporal coordination of neural activity in the brains of patients has more recently given the theory a neurophysiological basis (Friston, 1999; Friston and Frith, 1995; Lawrie et al, 2002; Scariati et al, 2016; Stephan et al, 2009). Consistent with this hypothesis, functional imaging studies in patients have repeatedly shown that schizophrenia weakens functional coupling in prefrontal networks based on reduced temporal correlations in BOLD signal across brain areas (Kang et al, 2011; Kubota et al, 2013; Lawrie et al, 2002; Mitelman et al, 2005; Mukherjee et al, 2016; Scariati et al, 2016; Tu et al, 2012, 2013). Measurements of brain activity at higher temporal resolution using electroencephalograms (EEG) and magnetoencephalography (MEG) have shown reduced synchrony in gamma band during task performance (Dale et al, 2016; Uhlhaas and Singer, 2015).…”
Section: Discussionmentioning
confidence: 79%
“…But neurophysiological evidence of impaired temporal coordination of neural activity in the brains of patients has more recently given the theory a neurophysiological basis (Friston, 1999; Friston and Frith, 1995; Lawrie et al, 2002; Scariati et al, 2016; Stephan et al, 2009). Consistent with this hypothesis, functional imaging studies in patients have repeatedly shown that schizophrenia weakens functional coupling in prefrontal networks based on reduced temporal correlations in BOLD signal across brain areas (Kang et al, 2011; Kubota et al, 2013; Lawrie et al, 2002; Mitelman et al, 2005; Mukherjee et al, 2016; Scariati et al, 2016; Tu et al, 2012, 2013). Measurements of brain activity at higher temporal resolution using electroencephalograms (EEG) and magnetoencephalography (MEG) have shown reduced synchrony in gamma band during task performance (Dale et al, 2016; Uhlhaas and Singer, 2015).…”
Section: Discussionmentioning
confidence: 79%
“…Although there is strong anatomical and functional connectivity between the vmPFC and OFC, on the one hand, and the amygdala, on the other (see above), and this connectivity is highly relevant for psychiatric disorders (Downar & Daskalakis, ; Kamphausen et al, ; Likhtik & Paz, ; Mukherjee et al, ; Myers‐Schulz & Koenigs, ; Park et al, ; A. K. Roy et al, ), the mFP was selected for TMS instead. The mFP is located both proximal to the scalp, which ensures effective stimulation with a conventional TMS coil (Downar & Daskalakis, ), and atop a medial brain circuit that includes pathways between vmPFC, OFC and amygdala (Forbes & Grafman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is strong anatomical and functional connectivity between the vmPFC and OFC, on the one hand, and the amygdala, on the other (see above), and this connectivity is highly relevant for psychiatric disorders (Downar & Daskalakis, 2013;Kamphausen et al, 2013;Likhtik & Paz, 2015;Mukherjee et al, 2016;Myers-Schulz & Koenigs, 2012;Park et al, 2018;A. K. Roy et al, 2013), the mFP was selected for TMS instead.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Amygdala–prefrontal connectivity is reduced in patients with schizophrenia during emotion perception (Bjorkquist, Olsen, Nelson, & Herbener, 2016) or emotional distractors (Mukherjee et al., 2016), and during bottom–up emotional processes (Comte et al., 2017). However, the tasks used in previous studies have involved emotional rather than cognitive conflict.…”
Section: Introductionmentioning
confidence: 99%